Inovasi Sobat Antar ObatKu: Optimalisasi Waktu Tunggu dan Kepuasan Pasien di RSIA Glamor Husada - Ainul Yaqin; Novi Anggraeni; Mustofa Haris; Hasinuddin; Amriani (LPPM STIKES Marendeng Majene, 2026)
Hospital pharmacy services are one of the hospital activities that support quality healthcare. Based on Ministry of Health Regulation No. 72 of 2016 on Standards for Pharmaceutical Services in Hospitals. Prescription waiting times also influence patients’ expectations regarding hospital services, particularly those of the hospital pharmacy department. The objective of this study was to analyze differences in medication queue waiting times between groups that implemented the “Sobat Antar ObatKu” method and those that did not at RSIA Glamor Husada. The research method used was a quasi-experimental design with a post-test control group design. Subjects were selected using simple random sampling, with a sample size of 45 outpatients at RSIA Glamor Husada. Data analysis was performed using a t-test. Analysis results: There was a difference in medication queue waiting times between the group that implemented the “Sobat Antar ObatKu” method and the group that did not implement the “Sobat Antar ObatKu” method at RSIA Glamor Husada. Hospital management is advised to maintain and develop the “Sobat Antar ObatKu” innovation because it has been proven to shorten medication service waiting times and improve outpatient satisfaction